Response Mechanisms of Plants Under Saline-Alkali Stress - Fang, Shumei; Hou, Xue; Liang, Xilong (Frontiers in Plant Science, 2021)
As two coexisting abiotic stresses, salt stress and alkali stress have severely restricted the development of global agriculture. Clarifying the plant resistance mechanism and determining how to improve plant tolerance to salt stress and alkali stress have been popular research topics. At present, most related studies have focused mainly on salt stress, and salt-alkali mixed stress studies are relatively scarce. However, in nature, high concentrations of salt and high pH often occur simultaneously, and their synergistic effects can be more harmful to plant growth and development than the effects of either stress alone. Therefore, it is of great practical importance for the sustainable development of agriculture to study plant resistance mechanisms under saline-alkali mixed stress, screen new saline-alkali stress tolerance genes, and explore new plant salt-alkali tolerance strategies. Herein, we summarized how plants actively respond to saline-alkali stress through morphological adaptation, physiological adaptation and molecular regulation.